Implementasi Prinsip – Prinsip Good Corporate Governance (GCG) pada Bank Syariah Indonesia KCP.Panyabungan Mandailing Natal - Asriani, Elza; Sari, Maya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to evaluate the application of the principles of Good Corporate Governance (GCG) at Bank Syariah Indonesia Kcp. Panyabungan Mandailing Natal. The implementation of GCG is very important for Islamic banks to ensure transparent, accountable, responsible, independent, and fair operations, in accordance with sharia principles. The research method used is a qualitative approach with a descriptive method, involving interviews with bank staff and direct observation at the research location. The results showed that Bank Syariah Indonesia Kcp. Panyabungan has implemented GCG principles well. Transparency is evident from the disclosure of accurate and timely information. Accountability is realized through the supervision and accountability of the board of commissioners and directors. The bank complies with laws and regulations and sharia principles as part of its responsibility. Independence is achieved through decision-making that is free from external pressure, while fairness is reflected in fair treatment to all stakeholders. Although the results show good GCG implementation, there is a need to continue strengthening GCG implementation to maintain the integrity and sustainability of the bank in the long run.